Profil Berat Badan Bayi Lahir dan Kadar Hematologi dengan Kejadian Asfiksia Neonatorum di RSUP Dr. Kariadi Semarang - Fany Bela Pratiwi; Listyaning Eko Martanti; Ida Ariyanti (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2023)
Infant mortality is a global health problem. Approximately 60% of these deaths were infants aged 7 days with perinatal disorders, one of which was asphyxia. Asphyxia neonatorum is the failure to breathe spontaneously and regularly immediately after the baby is born. The indicator of a newborn health is looking at the baby’s weight. Inadequate blood flow occurs so that it affects hematological levels which have an important role in the formation of immunity and the continuity of oxygen in the blood to all cells and tissues in the baby’s body. The design of research is descriptive quantitative with a single variable using a retrospective approach. This research was conducted from March to May 2022. The sampling method used a total sampling technique with a sample of 100 secondary data. Data analysis was performed using univariate analysis with descriptive statistical methods. The results showed that most of the babies had low birth weight of 67%. Hematology levels showed a normal scale, that is haemoglobin 78%, haematocrit 71%, erythrocytes 59%, and leukocytes 80%. The conclusion of this study is that most infants with asphyxia neonatorum have low birth weight and normal hematological levels. From the results of the study, it is hoped that the optimization of integrated ANC implementation, monitoring Body Mass Index of pregnant women, and anticipation of pregnancy problem can be carried out to reduce infant mortality cases, especially asphyxia